Genome-wide sequence transposon insertion sites and analyze the essential genes of Brucella melitensis. (November 2017) - De, Yanyan; Dong, Congyue; Cao, Yanyang; Wang, Xiaolei; Yang, Xiaowen; Wang, Ning; Zhang, Cunrui; Wang, Zhen; Lyu, Yanli; Wu, Qingmin
Abstract: A transposon mutant library of B. melitensis NI including 32, 640 transposon mutants was established. By sequencing the transposon insertion sites, 10, 832 mutants were successfully defined for their insertion sites. Analysis of the mutants with defined transposon insertion sites (DTIS) indicated that the insertions were well spread through the two genomes. In addition, 948 genes with no detectable transposon insertions were taken as the candidate for identification of essential genes. In comparison with the Bacterial Database of Essential Genes and by using comparative genomics analysis, 183 potential essential genes of B. melitensis NI cultured in vitro were found and they were conserved in the common bacteria. This work was focused on screening of the essential genes of B. melitensis NI, which may provide a foundation for identification of the novel drug targets against brucellosis. Besides, the sequence-defined transposon library should serve as a resource for screening of different function genes of Brucella . Highlights: A sequence-defined transposon mutant library of Brucella was constructed. 183 potential essential genes were predicted.